1990
DOI: 10.1016/0092-8674(90)90398-x
|View full text |Cite
|
Sign up to set email alerts
|

Correction of the cystic fibrosis defect in vitro by retrovirus-mediated gene transfer

Abstract: We have used retrovirus-mediated gene transfer to demonstrate complementation of the cystic fibrosis (CF) defect in vitro. Amphotropic retroviruses were used to transduce a functional cystic fibrosis transmembrane conductance regulator (CFTR) cDNA into CFPAC-1, a pancreatic adenocarcinoma cell line derived from a patient with CF that stably expresses the chloride transport abnormalities characteristic of CF. CFPAC-1 cells were exposed to control virus (PLJ) and CFTR-expressing virus (PLJ-CFTR); viral-transduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
219
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 566 publications
(229 citation statements)
references
References 26 publications
7
219
0
2
Order By: Relevance
“…CFPAC-PLJ subline represents a mock-transfected clone, and the CFPAC-PLJ-CFTR subline has been derived from a CFTR-expressing clone. The functionality of the CFTR protein has been demonstrated (Drumm et al, 1990). Our results show that cells expressing functional CFTR (CFPAC-PLJ-CFTR) have a decreased level (B50%) of MUC4 transcripts (Figure 1b) compared to the cells lacking CFTR function (CFPAC1 and CFPAC-PLJ).…”
Section: Cftr Expression Is Inversely Associated With Muc4 Expressionmentioning
confidence: 61%
See 1 more Smart Citation
“…CFPAC-PLJ subline represents a mock-transfected clone, and the CFPAC-PLJ-CFTR subline has been derived from a CFTR-expressing clone. The functionality of the CFTR protein has been demonstrated (Drumm et al, 1990). Our results show that cells expressing functional CFTR (CFPAC-PLJ-CFTR) have a decreased level (B50%) of MUC4 transcripts (Figure 1b) compared to the cells lacking CFTR function (CFPAC1 and CFPAC-PLJ).…”
Section: Cftr Expression Is Inversely Associated With Muc4 Expressionmentioning
confidence: 61%
“…Short-interfering RNA (siRNA)-mediated silencing of CFTR upregulates MUC4 expression CFPAC1 and derived sublines were generated more than a decade ago (Drumm et al, 1990) and have undergone numerous passages. Therefore, in order to ascertain that the differential MUC4 expression in CFPAC1 cells is indeed associated with CFTR, we employed an siRNA-mediated gene-silencing approach to validate the role of CFTR in MUC4 regulation.…”
Section: Cftr Expression Is Inversely Associated With Muc4 Expressionmentioning
confidence: 99%
“…Our findings showed a rapid and strong effect of ATP on mucin secretion by control epithelial cells and the reverted CF cells but no effect on the CFPAC-1 cells (original and mock-transfected). It has already been shown that the retrovirus-mediated transfection of cDNA for wild type CFTR into CFPAC-1 cells conferred cAMPdependent regulation of C1 conductance [19], alleviated the alteration of sulfate transport via an anion exchange mechanism [22] and corrected the defect in intracellular trafficking of the CF antigen [23].…”
Section: Discussionmentioning
confidence: 99%
“…CFPAC-1 is a pancreatic adenocarcinoma cell line derived from a homozygous patient for phenylalanine deletion at position 508 (AF 508) and expresses the appropriate CF gene product [18]. CFPAC-I cells were stably transfected with a retroviral vector (PLJ) that contained the full-length cDNA encoding wild type CFTR: CFPAC-PLJ-CFTR6 [19]. CFPAC-PLJ6 were CFPAC-1 cells exposed to control retrovirus alone (PLJ) [19].…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation